ENHANCING ARABIC VOCABULARY MASTERY THROUGH THE USE OF IMAGE MEDIA - Sustiana, Wenda; Zaki, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
In This study, the problem examined is how dhe use of visual media can enhance vocabulary mastery in Arabic language. The objective of this research is to describe dhe use of visual media in impriving vocabulary mastery in Arabic language for students. The benefits of this research for learners are anhanching their Arabic language proficiency. Meanwhile, the benefits for teachers include improving their skills in employing appropriate methods during the learning process and enhancing their ability to select more effective learning media. This research employs a qualitative approach using interview methods. Based on the findings, it is evident that the use of visual media can enhance vocabulary mastery in Arabic language learning. The steps for using visual media to improve Arabic vocabulary mastery are as follows: 1. The teacher presents images of vocabulary words to be taught, and students guess the word depicted; 2. The teacher provides the vocabulary words in Arabic: 3. Students repeart after the teacher; 4. Students memorize the new vocabulary words.